Serial writing in the minificcional text: threshold of the unstable generic cross in "Oficios de Noé" by Guillermo Bustamante Zamudio - Illas Ramírez, Wilfredo José Rafael (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
The idea of ​​miniature texts whose proposal aspires to integrate into larger narrative units characterized by the cohesion of the small fragments that constitute it, is an expression of the emergence of an aesthetic based on problematizing conceptual instances such as generic hybridity, rupture and transgression, border delocalisation and multiplicity of readings. In this sense, it is interesting to know how serial writing operates both in the construction of a seemingly integrated mini-universe, and in the reading exercise that, strictly speaking, disarms that fragile ideal of articulation to reiterate the predominance of the fragment in a narrative bet that before each new disposition, it raises unpublished places of resignification. In this way, the challenge of seriality necessarily postulates its counterpart and, in this parodic and ironic search, the impossibility of pigeonholing is reaffirmed. Seen this way, seriality is another way of reacting to genres, certainties and great stories.
Keywords: dilution; fragmentariness; hybridity; rupture; seriality; transgression